2021
DOI: 10.1111/bju.15316
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gleason grade and Gleason grade group at positive surgical margins: a systematic review and meta‐analysis

Abstract: To systematically review and perform a meta-analysis of studies investigating the role of primary Gleason grade (PGG), Gleason score (GS) or Gleason grade group (GGG) at positive surgical margins (PSMs) after radical prostatectomy (RP) in predicting biochemical recurrence (BCR) and oncological outcomes. MethodsA systematic search was conducted using the MEDLINE, Scopus, Embase and Cochrane databases according to Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. Studies pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…Gleason grade was another important biomarker in PC ( Sopyllo, Erickson & Mirtti, 2021 ; Moris et al, 2020 ). Recently, a meta-analysis found that Gleason grade was positively associated with recurrence after surgery ( John et al, 2021 ). Gleason scoring system mainly concentrated on the pathological structure of PC, while the transcriptomic and genomic features were missed.…”
Section: Discussionmentioning
confidence: 99%
“…Gleason grade was another important biomarker in PC ( Sopyllo, Erickson & Mirtti, 2021 ; Moris et al, 2020 ). Recently, a meta-analysis found that Gleason grade was positively associated with recurrence after surgery ( John et al, 2021 ). Gleason scoring system mainly concentrated on the pathological structure of PC, while the transcriptomic and genomic features were missed.…”
Section: Discussionmentioning
confidence: 99%
“…Gleason score of the tumor at the positive margin has also been associated with the prognosis [ 58 , 59 , 60 , 61 ], albeit in some studies it has been found that it is not an independent factor [ 47 ]. A recent meta-analysis of 10 retrospective cohort studies, found that primary Gleason grade 4 or 5 at the margin was predictive of biochemical-free recurrence [ 62 ]. Prognostic grade group (PGG) 1 at the margin has been shown to have biochemical recurrence rates [ 60 ] and cancer-specific survival [ 61 ] equivalent to those of negative margins.…”
Section: Pathologic Features Of Positive Margins With Clinical Significancementioning
confidence: 99%
“…However, the clinical significance of PSM after RP is controversial, with 27-44% of patients developing BCR, 6.8-24.3% with systemic progression, and prostate cancerrelated mortality ranging from 0.8% to 3.7% within 7-13 years of follow-up. 3 So far, several parameters associated with PSM, including Gleason grade and margin length at PSM as well as the location of PSM, were reported to be associated with BCR after RP. 3,5 Among these PSM-associated parameters, in a study by Matsuda et al, the impact of nerve sparing in RP on the location of PSM and its effect on BCR was investigated, and two important findings are reported.…”
mentioning
confidence: 99%
“…3 So far, several parameters associated with PSM, including Gleason grade and margin length at PSM as well as the location of PSM, were reported to be associated with BCR after RP. 3,5 Among these PSM-associated parameters, in a study by Matsuda et al, the impact of nerve sparing in RP on the location of PSM and its effect on BCR was investigated, and two important findings are reported. 6 One finding is that PSM in the anterior apex was not associated with the risk of BCR after RP.…”
mentioning
confidence: 99%
See 1 more Smart Citation